Positive strategies of language politeness across tourism service actors: A cross-cultural socio-pragmatic study - Elza Leyli Lisnora Saragih; Mulyadi Mulyadi; Khairina Nasution; Mhd. Pujiono (Research Journal in Advanced Humanities, 2023)
This paper discusses the language politeness strategy of tourism actors in the Lake Toba area. This study is very important considering that more and more people in the world are traveling to various countries for tourism. Therefore, cross-cultural communication must be intensified. This research is qualitative with a phenomenological approach. Data were collected through observation techniques, field notes, listening, recording, and in-depth interviews. Meanwhile, data analysis uses matching and distribution methods. The results of the study show that there are differences in the positive language politeness strategies used by tour operators towards English-speaking foreign tourists and domestic tourists. For domestic tourists, strategies are used to pay attention, use inter-group markers, show praise and sympathy, provide assistance and promises, give gifts, joke, be optimistic, and give reasons. Tourist actors do not use optimism and joke strategies when communicating with foreign tourists. Tourist actors use positive politeness strategies to show respect, sympathy, persuade, please tourists, familiarize themselves, advise, and apologize.